2018
DOI: 10.1029/2017wr021855
|View full text |Cite
|
Sign up to set email alerts
|

Geophysics‐Based Contaminant Mass Discharge Quantification Downgradient of a Landfill and a Former Pharmaceutical Factory

Abstract: Contaminant mass discharge is a commonly applied tool to evaluate the environmental impact of contaminated sites on water resources. At large contaminated sites with heterogeneous sources, such as landfills, the number of wells available is often not sufficient, leading to a high uncertainty of mass discharge estimates. In this study, we tackle the uncertainty of the contaminant mass discharge due to low sampling densities by interpolating limited water‐sample data with the support of surface direct current re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…Note that degradation will not be a limitation as long as the compounds remain, however, it may be difficult to apply the method if the composition of compounds in the plume changes due to, for example, sequential degradation. For instance, the method could not be applied for the chlorinated ethenes due to reductive dechlorination taking place in the aquifer somewhere between the source and the stream (Rønde et al ; Balbarini et al ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that degradation will not be a limitation as long as the compounds remain, however, it may be difficult to apply the method if the composition of compounds in the plume changes due to, for example, sequential degradation. For instance, the method could not be applied for the chlorinated ethenes due to reductive dechlorination taking place in the aquifer somewhere between the source and the stream (Rønde et al ; Balbarini et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Groundwater and hyporheic zone water samples collected below the streambed showed that groundwater contaminated by pharmaceutical compounds discharges along a 2‐km stretch of the stream (Rasmussen et al ; Sonne et al ). A discharge area (red rectangle in Figure ) with high groundwater concentrations of benzene, chlorinated ethenes, mainly cis DCE ( cis ‐1,2‐dichloroethene) and vinyl chloride (VC), and pharmaceutical compounds was found (Rønde et al ; Sonne et al ; Balbarini et al ). Outside this area, chlorinated ethenes were only found to enter the stream in low concentrations, in contrast to the pharmaceutical compounds, which entered the stream over a larger area (Sonne et al ).…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations